Low-cost, low-viscosity, high-toughness and weather-resistant three-proofing UV (ultraviolet) adhesive and preparation method thereof

By optimizing the composition and preparation process of conformal UV adhesives, the problems of high cost, high viscosity, and uneven toughness and adhesion of traditional conformal adhesives have been solved. This has resulted in a low-cost, low-viscosity, high-toughness, and high-adhesion environmentally friendly conformal UV adhesive suitable for electronic assembly fields such as printed circuit boards.

CN121108927APending Publication Date: 2025-12-12WEIFANG SHENGDA PLASTIC

Patent Information

Application Number
CN202511676005.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-17
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Existing conformal adhesives suffer from problems such as high cost, high viscosity, difficult application, and an inability to balance toughness and adhesion. Furthermore, traditional solvent-based conformal paints have a strong odor and fail to meet environmental protection requirements.

Method used

A low-cost formulation, comprising a combination of polyurethane acrylate oligomers, reactive diluents, photoinitiators, polymerization inhibitors, toughening agents, and coupling agents, is used to prepare a low-viscosity, high-toughness, weather-resistant, UV-resistant adhesive after stirring in a homogenizer. The different acrylate oligomers are combined to form a tight three-dimensional network structure to improve toughness and adhesion.

Benefits of technology

This invention achieves a low-cost, low-viscosity, high-toughness, and high-adhesion UV-resistant adhesive with good adaptability to high-temperature and high-humidity environments. After curing, the surface has high gloss and good transparency, and excellent adhesion and toughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121108927A_ABST
    Figure CN121108927A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of UV adhesive production, in particular to a low-cost, low-viscosity, high-toughness and weather-resistant three-proofing UV adhesive and a preparation method thereof.The low-cost, low-viscosity, high-toughness and weather-resistant three-proofing UV adhesive is prepared from, by weight, 40%-60% of urethane acrylate oligomer, 20%-48% of reactive diluent, 2%-5% of photoinitiator, 0.05%-0.2% of polymerization inhibitor, 1%-5% of flexibilizer and 1%-3% of coupling agent. The invention provides an environment-friendly three-proofing UV (ultraviolet) adhesive with low cost, low viscosity, high toughness and high weather resistance. The defects that a traditional adhesive is high in cost, high in viscosity, difficult to construct and incapable of balancing toughness and adhesive strength are overcome by optimizing the addition of a polyurethane acrylate oligomer, a reactive diluent and an auxiliary agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of UV adhesive production technology, specifically to a low-cost, low-viscosity, high-toughness, weather-resistant, three-proof UV adhesive and its preparation method. Background Technology

[0002] With the rapid development of electronic products, the application of UV-curable adhesives is becoming increasingly widespread. The diversification of production and life has led to the rapid development of the electronic assembly industry, while people's requirements for product quality and performance are also increasing. Especially for the printed circuit board industry, the search for conformal adhesives that are low in odor, fast in efficiency, moisture-proof, corrosion-proof, and salt spray-proof is being increasingly valued by manufacturers.

[0003] Currently, solvent-based conformal coatings remain the mainstream products on the market, characterized by their low price, simple application equipment, and good fluidity. However, traditional solvent-based conformal coatings have a strong odor, which contradicts environmental protection requirements. UV-cured conformal adhesives can effectively solve these problems. UV-cured conformal adhesives have low odor, fast curing speed, and simple equipment operation, reducing defects caused by human error. They are more versatile and perform well in humid, high-temperature, and acidic / alkaline environments, and are currently gaining popularity among manufacturers. Conformal adhesives on the market include epoxy resins, which have high adhesion and hardness but are difficult to rework; and silicone resins, which are heat-resistant and elastic, but have low adhesion. Dual-curing adhesive systems are costly and lack versatility. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a low-cost, low-viscosity, high-toughness, weather-resistant, UV-resistant adhesive and its preparation method, specifically achieved through the following technical solution: A low-cost, low-viscosity, high-toughness, weather-resistant, and UV-resistant adhesive comprises the following raw materials by weight percentage: 40-60% polyurethane acrylate oligomer, 20-48% reactive diluent, 2-5% photoinitiator, 0.05-0.2% polymerization inhibitor, 1-5% toughening agent, and 1-3% coupling agent; The polyurethane acrylate oligomer is selected from difunctional aliphatic polyurethane acrylate, hexafunctional aliphatic polyurethane acrylate, and epoxy acrylate mixed in a weight ratio of 28-45: 5: 7-12.

[0005] The reactive diluent is selected from one or a mixture of several of the following monofunctional reactive monomers: hydroxyethyl acrylate, isobornyl acrylate, tetrahydrofuran acrylate, lauryl acrylate, 1,6-hexanediol diacrylate, and tripropylene glycol diacrylate.

[0006] The coupling agent is selected from one or a mixture of any of the following silane coupling agents: KH550, KH560, and KH570.

[0007] The toughening agent is selected from one or a mixture of any of the following: dioctyl phthalate, dibutyl phthalate, dioctyl adipate, and dioctyl sebacate.

[0008] The polymerization inhibitor is hydroquinone.

[0009] The polyurethane acrylate oligomers are selected from difunctional aliphatic polyurethane acrylate, hexafunctional aliphatic polyurethane acrylate, and epoxy acrylate mixed in a weight ratio of 33:5:12.

[0010] The process includes the following steps: Weigh out the polyurethane acrylate oligomer, reactive diluent, photoinitiator, polymerization inhibitor, toughening agent, and coupling agent according to the formula, put them into a homogenizer and stir evenly, then let them air dry to room temperature.

[0011] The homogenizer operates at a rotational speed of 1200 revolutions to 600 rotations.

[0012] The invention has the following advantages: This invention provides a low-cost, low-viscosity, high-toughness, and high-weather-resistant environmentally friendly conformal adhesive. By optimizing the addition of polyurethane acrylate oligomers, reactive diluents, and additives, it overcomes the shortcomings of traditional adhesives, such as high cost, high viscosity, difficult application, and an inability to balance toughness and adhesion. After curing, the surface exhibits high gloss and good transparency, and maintains high adhesion and toughness even under high temperature and humidity conditions. Attached Figure Description

[0013] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the accompanying drawings used in the description of the specific embodiments or the prior art will be briefly introduced below.

[0014] Figure 1 The infrared spectrum of the adhesive; Figure 2 This is a bar chart showing the curing shrinkage rate before and after curing in some embodiments; Figure 3 These are morphological images under a high-resolution CCD microscope after 168 hours of high temperature and humidity in some embodiments. Detailed Implementation

[0015] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0016] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0017] This invention provides a low-cost, low-viscosity, high-toughness, weather-resistant, UV-resistant adhesive, comprising the following raw materials by weight percentage: 40-60% polyurethane acrylate oligomer, 20-48% reactive diluent, 2-5% photoinitiator, 0.05-0.2% polymerization inhibitor, 1-5% toughening agent, and 1-3% coupling agent.

[0018] The polyurethane acrylate oligomer is selected from at least two of the following: difunctional aliphatic polyurethane acrylate (such as 6157B-30 and 6148J-75 from Changxing Company, YC2200 from Shanghai Yinchang Company, and 6224D from Jiangsu Sanmu Company), hexafunctional aliphatic polyurethane acrylate (such as 6145-100 from Changxing Company and U-25-20D from Covestro Company), and epoxy acrylate (YC1181 from Shanghai Yinchang Company).

[0019] The reactive diluent is selected from one or a mixture of several of the following monofunctional reactive monomers: hydroxyethyl acrylate, isobornyl acrylate, tetrahydrofuran acrylate, lauryl acrylate, 1,6-hexanediol diacrylate, and tripropylene glycol diacrylate.

[0020] The coupling agent is selected from one or a mixture of any of the silane coupling agents KH550, KH560, and KH570.

[0021] The toughening agent is selected from one or a mixture of any of the following: dioctyl phthalate, dibutyl phthalate, dioctyl adipate, and dioctyl sebacate, all from Qilu Petrochemical Company.

[0022] Hydroquinone is used as the polymerization inhibitor.

[0023] The difunctional polyurethane acrylate used in this formulation employs aliphatic polyols with larger molecular weights to increase the content of flexible segments, while the difunctional polyurethane acrylate provides a low crosslinking density, resulting in acrylic oligomers with better flexibility.

[0024] The addition of hexafunctional polyurethane acrylate, in which the multifunctional carbon-carbon double bonds provide crosslinking points, enables it to form a more compact three-dimensional network structure, thereby improving its resistance to damage to the molecular chain in high temperature and high humidity environments.

[0025] The steric hindrance effect of epoxy acrylate balances the curing shrinkage caused by high crosslinking density, thus improving adhesion. Different reactive diluents can be used to create low-cost, low-viscosity, high-toughness, weather-resistant, UV-resistant adhesives.

[0026] By combining three different types of acrylate oligomers (hexafunctional polyurethane acrylate provides high crosslinking, epoxy acrylate balances the curing shrinkage caused by the high crosslinking of hexafunctional resin, and difunctional resin provides excellent flexibility), the final product achieves high toughness, high adhesion, and resistance to high temperature and humidity at a low cost.

[0027] In this invention, the photoinitiator is a mixture of photoinitiator TPO and photoinitiator 184.

[0028] The aforementioned low-cost, low-viscosity, high-toughness, weather-resistant, and UV-resistant adhesive is prepared using the following method: Polyurethane acrylate oligomer, reactive diluent, photoinitiator, polymerization inhibitor, toughening agent, and coupling agent are weighed according to the formula and placed in a homogenizer. The mixture is stirred at a rotation speed of 1200 revolutions to 600 rotations until homogeneous. After stirring, it is allowed to air dry to room temperature to obtain the UV-curable adhesive, which is then sealed and packaged. The infrared spectrum of the final product is shown below. Figure 1 As shown.

[0029] Through append Figure 1 It can be seen that 3381cm -1 The absorption peak corresponds to the characteristic peak of the NH bond, 1721 cm⁻¹. -1 The absorption peak represents the characteristic peak of the ester bond, 810 cm⁻¹. -1 With 1636cm -1 The absorption peak represents the characteristic peak of the acrylic double bond. These characteristic peaks indicate that the adhesive's main component is a polyurethane-acrylic system. (1271 cm⁻¹) -1 1181cm -1 1058cm -1 The absorption peaks represent characteristic peaks of ether bonds. Infrared spectroscopy reveals that the entire system is composed of polyurethane acrylic acid and epoxy acrylate systems.

[0030] The present invention will now be described in detail through specific embodiments.

[0031] The components of the three-proof UV adhesives of Examples 1 to 5 are shown in Table 1 below.

[0032] Table 1. Components of the UV-resistant adhesives used in Examples 1 to 5

[0033] According to Table 1, weigh out the polyurethane acrylate oligomer, reactive diluent, photoinitiator, toughening agent, coupling agent, etc., and put them into a homogenizer. Stir at a rotation speed of 1200 revolutions / rotations for 10 minutes. Stir until uniform, let it air dry to room temperature to obtain the light-cured adhesive, and then seal it in a package.

[0034] Example 6 22.5 parts of difunctional polyurethane acrylate (YC2200), 22.5 parts of epoxy acrylate (YC1181), 5 parts of hexafunctional aliphatic polyurethane acrylate, 35 parts of tetrahydrofuran acrylate, 5 parts of isobornyl acrylate, 5 parts of 1,6-hexanediol diacrylate, 2.5 parts of photoinitiator TPO, 1.5 parts of photoinitiator 184, 2 parts of toughening agent DOP, 0.1 parts of polymerization inhibitor hydroquinone, and 1.5 parts of coupling agent KH560 are placed in a homogenizer and stirred at a rotation speed of 1200 revolutions to 600 revolutions per minute for 10 minutes until homogeneous. The mixture is then allowed to air dry to room temperature to obtain a UV-cured adhesive, which is then sealed and packaged.

[0035] Example 7 30 parts of difunctional polyurethane acrylate (YC2200), 15 parts of epoxy acrylate (YC1181), 5 parts of hexafunctional aliphatic polyurethane acrylate, 35 parts of tetrahydrofuran acrylate, 5 parts of isobornyl acrylate, 5 parts of 1,6-hexanediol diacrylate, 2.5 parts of photoinitiator TPO, 1.5 parts of photoinitiator 184, 2 parts of toughening agent DOP, 0.1 parts of polymerization inhibitor hydroquinone, and 1.5 parts of coupling agent KH560 are placed in a homogenizer and stirred at a rotation speed of 1200:600 for 10 minutes until homogeneous. The mixture is then allowed to air dry to room temperature to obtain a UV-cured adhesive, which is then sealed and packaged.

[0036] The conformal adhesive prepared in the examples was subjected to performance testing. The performance testing methods of the examples are described in detail below: UV curing conditions: UV curing is performed using LED lamps with a main wavelength of 365nm, and the radiation intensity is 500-600mW / cm². 2 Curing time: 20 seconds.

[0037] High temperature and high humidity curing conditions: After bonding PC and PC sheets, place them in a programmable high temperature and high humidity chamber at 85℃ and 85% humidity for 168 hours, and then test the shear force attenuation rate before and after placement.

[0038] Viscosity test conditions: NDJ-5S viscosity meter, use #1 rotor at 30r / min to test three times and take the average value; Elongation at break test conditions: Three tests were conducted using a universal tensile testing machine under the national standard GB / T528-2009, and the average value was taken.

[0039] Adhesion test: 3M tape cross-cut adhesion test.

[0040] The test results are shown in Table 2 below.

[0041] Table 2 shows the detection results of the embodiments.

[0042] Table 3. Components of UV-resistant adhesives from Examples 8 to 10

[0043] Table 4 shows the test results of Examples 8 to 10.

[0044] The three-proof adhesive of the present invention has moderate viscosity, no volatile solvent added, good toughness, high bonding reliability, and all adhesion tests reach 5B. Moreover, the adhesion attenuation after high temperature and high humidity is optimal at 30% to 32%.

[0045] Through append Figure 2 It can be seen that the combination of difunctional polyurethane acrylate and epoxy acrylate in Example 4 resulted in the lowest curing shrinkage. A comparison between Examples 1 and 5 revealed that the addition of hexafunctional polyurethane acrylate led to increased overall curing shrinkage. Adding epoxy acrylate further reduced the increase in curing shrinkage caused by the addition of multiple functional groups. This is because the polymerization process of epoxy acrylate involves both van der Waals forces causing shrinkage of covalent bonds and intramolecular ring opening leading to volume increase, which is reflected in reduced volume shrinkage throughout the curing process.

[0046] Through append Figure 3 It is known that without the addition of hexafunctional resin, the adhesive is severely damaged by moisture under high temperature and humidity, resulting in various cracks and failure phenomena. However, the adhesive with the addition of hexafunctional resin is not easily damaged by moisture under high temperature and humidity due to the good cross-linking between molecules.

[0047] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A low-cost, low-viscosity, high-toughness, weather-resistant, UV-resistant adhesive, characterized in that, By weight percentage, it includes the following raw materials: 40-60% polyurethane acrylate oligomer, 20-48% reactive diluent, 2-5% photoinitiator, 0.05-0.2% polymerization inhibitor, 1-5% toughening agent, and 1-3% coupling agent; The polyurethane acrylate oligomer is selected from difunctional aliphatic polyurethane acrylate, hexafunctional aliphatic polyurethane acrylate, and epoxy acrylate mixed in a weight ratio of 28-45:5:7-12.

2. The low-cost, low-viscosity, high-toughness, weather-resistant, UV-resistant adhesive according to claim 1, characterized in that, The reactive diluent is selected from one or a mixture of several of the following monofunctional reactive monomers: hydroxyethyl acrylate, isobornyl acrylate, tetrahydrofuran acrylate, lauryl acrylate, 1,6-hexanediol diacrylate, and tripropylene glycol diacrylate.

3. The low-cost, low-viscosity, high-toughness, weather-resistant, UV-resistant adhesive according to claim 1, characterized in that, The coupling agent is selected from one or a mixture of any of the following silane coupling agents: KH550, KH560, and KH570.

4. The low-cost, low-viscosity, high-toughness, weather-resistant, UV-resistant adhesive according to claim 1, characterized in that, The toughening agent is selected from one or a mixture of any of the following: dioctyl phthalate, dibutyl phthalate, dioctyl adipate, and dioctyl sebacate.

5. The low-cost, low-viscosity, high-toughness, weather-resistant, UV-resistant adhesive according to claim 1, characterized in that, The polymerization inhibitor is hydroquinone.

6. The low-cost, low-viscosity, high-toughness, weather-resistant, UV-resistant adhesive according to claim 1, characterized in that, The polyurethane acrylate oligomers are selected from difunctional aliphatic polyurethane acrylate, hexafunctional aliphatic polyurethane acrylate, and epoxy acrylate mixed in a weight ratio of 33:5:

12.

7. The preparation method of the low-cost, low-viscosity, high-toughness, weather-resistant, UV-resistant adhesive according to claim 1, characterized in that, Includes the following steps: Weigh out the polyurethane acrylate oligomer, reactive diluent, photoinitiator, polymerization inhibitor, toughening agent, and coupling agent according to the formula, put them into a homogenizer and stir evenly, then let them air dry to room temperature.

8. The preparation method of the low-cost, low-viscosity, high-toughness, weather-resistant, UV-resistant adhesive according to claim 7, characterized in that, The homogenizer operates at a rotational speed of 1200 revolutions to 600 rotations.

Citation Information

Patent Citations

  • Ultraviolet curing adhesive capable of being quickly cured at low energy and preparation method of ultraviolet curing adhesive

    CN106753183A

  • Low-viscosity environmental-friendly UV / moisture dual-curing three-proofing adhesive and preparation method thereof

    CN109370507A

  • Solvent-free UV curing gloss oil and preparation method thereof

    CN114716902A

  • Radiation curable sealant used for encapsulating glasses nameplates or decorations

    WO2012013028A1

  • Visible light curable glue and preparation method therefor

    WO2017219619A1

Cited By

  • High-toughness UV dissociation glue for glass and preparation method of high-toughness UV dissociation glue

    CN121873735A